Transcriptomic analysis of koi (Cyprinus carpio) spleen tissue upon cyprinid herpesvirus 3 (CyHV3) infection using next generation sequencing. (February 2016) - Lee, Xuezhu; Yi, Yang; Weng, Shaoping; Zeng, Jie; Zhang, Hetong; He, Jianguo; Dong, Chuanfu
Abstract: Cyprinid Herpesvirus 3 (CyHV-3) can infect and specifically cause a huge economic loss in both common carp ( Cyprinus carpio ) and its ornamental koi variety. The molecular mechanisms underlying CyHV-3 infection are not well understood. In this study, koi spleen tissues of both mock and CyHV-3 infection groups were collected, and high-throughput sequencing technology was used to analyze the differentially expressed genes (DEGs) at the transcriptome level. A total of 105, 356, 188 clean reads from two libraries were obtained. After the de novo assembly of the transcripts, 129, 314 unigenes were generated. Of these unigenes, 70, 655 unigenes were matched to the known proteins in the database, while 2190 unigenes were predicted by ESTScan software. Comparing the infection group to the mock group, a total of 23, 029 significantly differentially expressed unigenes were identified, including 10, 493 up-regulated DEGs and 12, 536 down-regulated DEGs. GO (Gene Ontology) annotation and functional enrichment analysis indicated that all of the DEGs were annotated into GO terms in three main GO categories: biological process, cellular component and molecular function. KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis of the DEGs showed that a total of 12, 002 DEG unigenes were annotated into 256 pathways classified into 6 main categories. Additionally, 20 differentially expressed genes were validated by quantitative real-time PCR. As the first report of a transcriptome analysis of koi carp with CyHV-3 infection, the data presented here provide knowledge of the innate immune response against CyHV-3 in koi carp and useful data for further research of the molecular mechanism of CyHV-3 infection. Highlights: First transcriptome of koi spleen response to CyHV-3 infection using Illumina Hiseq 2500. A total of 129, 314 unigenes were obtained from two libraries through de novo assembly. Totally 23, 029 DEGs were identified, including 10, 493 up-regulated DEGs and 12, 536 down-regulated DEGs. Twenty of differently expressed genes were selected for validation with RT-qPCR. Immune-related genes involved in CyHV-3 infection were identified.